Application of tension to prerigor goat carcasses to improve cooked meat tenderness. (January 2019) - Basinger, Kelsey L.; Shanks, Bruce C.; Apple, Jason K.; Caldwell, James D.; Yancey, Janeal W.S.; Backes, Elizabeth A.; Wilbers, Luke S.; Johnson, Tim M.; Bax, Amy L.
Abstract: In two separate experiments, carcasses of intact Kiko × Boer male kids were assigned randomly to tension treatments applied 30 min postmortem: 1) suspended by the Achilles tendon (AT); 2) suspended from the pelvic bone with front and hind legs tied together (TS); or 3) suspended by the Achilles tendon, and the fore- and hindsaddle were separated at the 12th/13th thoracic intervertebral disk, external fat, accessory muscles and epimysium surrounding the longissimus muscle (LM) were cut (TC), and a 2.3-kg weight attached to the neck (TC + W). Warner-Bratzler shear force values for the LM were reduced ( P  < 0.05) 24.4 to 35.9 N in TS carcasses compared to AT carcasses, and WBSF values of SM from TS carcasses were 25.0 and 20.3 N less ( P  < 0.05) than those for AT and TC + W carcasses, respectively. Results indicated that cooked goat meat tenderness, particularly the LM and SM, may be improved greatly by suspending goat carcasses by the pelvic bone. Highlights: Prerigor "Tenderstretch" application increased sarcomere lengths of the longissimus muscle by more than 10%. "Tenderstretch" application effectively decreased shear force (SF) values of goat longissimus and semimembranosus muscles. When weight was added to the "Tendercut" treatment, sarcomere length was increased, but SF values were only reduced in the longissimus thoracis . "Tenderstretch" can be easily applied to prerigor goat carcasses to improve cooked goat meat tenderness.